1985
DOI: 10.1007/bf01799458
|View full text |Cite
|
Sign up to set email alerts
|

Lymphoid cell lines as a model system for the study of Wolman's disease: Enzymatic, metabolic and ultrastructural investigations

Abstract: Epstein-Barr virus (EBV) transformed lymphoid cell lines (LCL) were established from blood lymphocytes of a patient affected with Wolman's disease (WD) and from her parents. These LCL showed a severe deficiency in acid lipase activity using every substrate in comparison to LCL from normal subjects, in which acid lipase activity was similar to that in blood lymphocytes. In the LCL from Wolman's disease a major accumulation of neutral lipids was observed, mainly cholesteryl esters, CE (amount around 7 times high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
1

Year Published

1987
1987
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 20 publications
2
13
1
Order By: Relevance
“…These conclusions do not agree with the hypothetical role of the lysosomal lipase in cytoplasmic triacylglycerol catabolism of differentiating myoblasts suggested by Sauro et al [18]. Our previous enzymatic data, briefly summarized in Materials and Methods [25], and the present results suggest the existence in fibroblasts of a neutral lipase able to hydrolyse cytoplasmic triacylglycerols: this enzyme could be identical to that described by Hoeg et al [31]. The metabolic data reported here demonstrate that such a lipase is active in Wolman fibroblasts in spite of the observation of Messieh et al [32] who reported an abnormal neutral lipase activity in these cells.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…These conclusions do not agree with the hypothetical role of the lysosomal lipase in cytoplasmic triacylglycerol catabolism of differentiating myoblasts suggested by Sauro et al [18]. Our previous enzymatic data, briefly summarized in Materials and Methods [25], and the present results suggest the existence in fibroblasts of a neutral lipase able to hydrolyse cytoplasmic triacylglycerols: this enzyme could be identical to that described by Hoeg et al [31]. The metabolic data reported here demonstrate that such a lipase is active in Wolman fibroblasts in spite of the observation of Messieh et al [32] who reported an abnormal neutral lipase activity in these cells.…”
Section: Discussioncontrasting
confidence: 84%
“…Experiments were performed in duplicate using a radiochromatographic scanner (Berthold LB 2842 automatic TLC linear analyser). Non-labelled cellular lipids were analysed as previously reported [25]: free and total cholesterol from the lipid extract were determined by gas chromatography (Intersmat, model 120 DFL; methylsilicon capillary column SP2100, 20 m, 0.3 nm internal diameter) according to the procedure of Ambert et al [26] using 5-a-cholestane as internal standard. Triacylglycerols were separated by TLC on silica gel (petroleum ether/diethyl ether/acetic acid, 80/20/1, v/v/v), eluted and determined by gas chromatography (Intersmat 120DFL, SP2100 capillary column; oven temperature programmed from 290°C to 335"C, 6"C/min; flame ionization detector Fibroblasts were cultivated during 6 days in culture medium containing 10% fetal calf serum without (FCS) or with (LP-MI and LP-M2) hyperlipemic serum (pool of sera from hypertriglyceridemic type IV patients, heat-treated for 1 h at 56°C and sterilized by filtration on micropore 0.22 pm).…”
Section: Fig I Time-dependent Kinetics Of Radiolabelled Lipids Aftementioning
confidence: 99%
“…The use of LCLs has been previously proven to be instrumental in uncovering important pathogenic mechanisms in other diseases, such as hypertension, glycogen and lipid storage diseases, chronic granulomatous disease, hematologic disorders, and solid tumors (27)(28)(29)(30)(31)(32)(33). One illustrative example is essential hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…The fatty acids liberated were quantified radiometrically and fluorometrically as in [18,19]. Proteins were determined by the method of Lowry et al [20].…”
Section: Methodsmentioning
confidence: 99%